Strength-frequency curve for micromagnetic neurostimulation through excitatory postsynaptic potentials (EPSPs) on rat hippocampal neurons and numerical modeling of magnetic microcoil (μcoil). (4th February 2022) - Saha, Renata; Faramarzi, Sadegh; Bloom, Robert P; Benally, Onri J; Wu, Kai; di Girolamo, Arturo; Tonini, Denis; Keirstead, Susan A; Low, Walter C; Netoff, Theoden I; Wang, Jian-Ping
Abstract: Objective. The objective of this study was to measure the effect of micromagnetic stimulation ( μ MS) on hippocampal neurons, by using single microcoil ( μ coil) prototype, magnetic pen (MagPen). MagPen will be used to stimulate the CA3 region magnetically and excitatory post synaptic potential (EPSP) response measurements will be made from the CA1 region. The threshold for micromagnetic neurostimulation as a function of stimulation frequency of the current driving the µ coil will be demonstrated. Finally, the optimal stimulation frequency of the current driving the μ coil to minimize power will be estimated. Approach. A biocompatible, watertight, non-corrosive prototype, MagPen was built, and customized such that it is easy to adjust the orientation of the μ coil and its distance over the hippocampal tissue in an in vitro recording setting. Finite element modeling of the μ coil design was performed to estimate the spatial profiles of the magnetic flux density (in T) and the induced electric fields (in V m −1 ). The induced electric field profiles generated at different values of current applied to the µ coil can elicit a neuronal response, which was validated by numerical modeling. The modeling settings for the μ coil were replicated in experiments on rat hippocampal neurons. Main results. The preferred orientation of MagPen over the Schaffer Collateral fibers was demonstrated such that they elicit a neuron response. The recorded EPSPs from CA1 region due to μ MS at CA3 region were validated by applying tetrodotoxin (TTX). Application of TTX to the hippocampal slice blocked the EPSPs from μ MS while after prolonged TTX washout, a partial recovery of the EPSP from μ MS was observed. Finally, it was interpreted through numerical analysis that increasing frequency of the current driving the μ coil, led to a decrease in the current amplitude threshold for micromagnetic neurostimulation. Significance. This work reports that micromagnetic neurostimulation can be used to evoke population EPSP responses in the CA1 region of the hippocampus. It demonstrates the strength-frequency curve for µ MS and its unique features related to orientation dependence of the µ coils, spatial selectivity and stimulation threshold related to distance dependence. Finally, the challenges related to µ MS experiments were studied including ways to overcome them.